Regulation of electromotility in the cochlear outer hair cell - Frolenkov, Gregory I (Blackwell Science Inc, 2006)
Mechanosensory outer hair cells play an essential role in the amplification of sound-induced vibrations within the mammalian cochlea due to their ability to contract or elongate following changes of the intracellular potential. This unique property of outer hair cells is known as electromotility. Selective efferent innervation of these cells within the organ of Corti suggests that regulation of outer hair cell electromotility may be the primary function of the efferent control in the cochlea. A number of studies demonstrate that outer hair cell electromotility is indeed modulated by the efferent neurotransmitter, acetylcholine. The effects of acetylcholine on outer hair cells include cell hyperpolarization and a decrease of the axial stiffness, both mediated by intracellular Ca(2+). This article reviews these results and considers other potential mechanisms that may regulate electromotility, such as direct modification of the plasma membrane molecular motors, alteration of intracellular pressure, and modification of intracellular chloride concentration.